CONNECTION OF ANIMATION AND MATHEMATICS FOR DESCRIPTION OF IDEAL GAS STATE CHANGES - FILÍPEK, Josef; NAVRÁTIL, Miroslav (Trends in education, 2009)
The paper presents continuous changes of state quantities of ideal gas during isothermal and adiabatic compression depending on the degree of external force. Mutual relationships are illustrated with the use of animated models, spatial and area diagrams, including mathematical derivation of the volume work performed by the system.
Keywords: state changes of gas; animated models; gas work.